Lived experiences of breast cancer survivors after diagnosis, treatment and beyond: qualitative study. (7th May 2015) - Williams, Faustine; Jeanetta, Stephen C.
Abstract: Background: The number of breast cancer survivors has increased since 1990 due to advances in biomedical technology that lead to an increase in early diagnosis and treatment. Research on survivorship has focused on the psychological and treatment aspects of the disease. The goal of this study was focused on exploring the lived experiences of breast cancer survivors from diagnosis, treatment and beyond. Objective: To understand the lived experiences of women who are breast cancer survivors. Design, Setting and Participants: A purposive sampling strategy was used to recruit participants from two Missouri cancer centres. A total of 15 women breast cancer survivors were interviewed. Findings: Three major themes emerged that described the lived experiences of the women. These were factors from the diagnosis and treatment management impacting survivorship, relationship and support system and implication of survivorship. Participants noted that coping with the diagnosis and treatment was a stressful journey and required lots of adjustment and changes. Some developed various techniques such as journaling their activities which provided comfort. In addition, support from family was shared as the key which gave them strength and courage through the different stages of treatment. However, they found it difficult to articulate what survivorship meant. Conclusion: Using in‐depth interview techniques, this study shed light on the experiences of women who were diagnosed with breast cancer and have completed treatment. They acknowledged frustration with their diagnosis and body changes. Support received from family and friends helped them cope through their treatment. However, they felt abandoned once the treatment phase was over and were uncertain what survivorhood meant to them.